Security Sector Reform in Post-Conflict States in Africa: The Case of Liberia - Harrison-Cudjoe, S. (University of Ghana, 2012)
The study analyses post-conflict Security Sector Reform (SSR) in post-conflict states in Africa with particular reference to Liberia. It posits that a robust and comprehensive SSR can be a tool for peacebuilding, and promote sustainable peace in postconflict environments. The importance of local ownership to any attempt at carrying out an SSR is also discussed in the study. This helps to make meaningful generalisations about, and contribute to post-conflict SSR as a whole. The study finds that effective and sustainable SSR in postconflict societies is possible within the context of a multi-sectoral approach. This will involve the combined efforts of all the management and oversight bodies such as the Legislature, Judiciary and the Executive to achieve result. The role of civil society in ensuring the sustainability of any SSR program is also highlighted. The study makes the recommendation, among others, that in future the ECOWAS Mechanism should be applied as an SSR tool for sub-regional transformation to prevent a recurrence of violence.
Thesis (MPHIL)-University of Ghana, 2012